2017
DOI: 10.1620/tjem.241.149
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiles in Pericardial Effusion in a Down Syndrome Infant with Transient Abnormal Myelopoiesis

Abstract: Infants with Down Syndrome (DS) are at risk of developing a transient abnormal myelopoiesis (TAM). TAM is characterised by increased circulating blast cells but usually self-limiting. DS patients with TAM sometimes show fetal hydrops and effusion in body cavities, but the mechanism remains unclear. We report here a case of infant with DS who had pericardial effusion, TAM, and eosinophilia. In her pericardial effusion, white blood cell count was 6.0 × 10 3 /µL, 41% of which were eosinophils. After administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…In Table , we summarize the literature reports of patients with DS‐ and TAM‐associated PE. From the reported cases, three cases presented an increased number of eosinophils in the PE, and in two cases, there are no mentions of the cytological aspects of PE …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In Table , we summarize the literature reports of patients with DS‐ and TAM‐associated PE. From the reported cases, three cases presented an increased number of eosinophils in the PE, and in two cases, there are no mentions of the cytological aspects of PE …”
Section: Discussionmentioning
confidence: 95%
“…Kusanagi et al suggest that eosinophilic infiltration at the cardiac site may have caused direct heart damage and failure or that the degranulation of the eosinophils caused PE and consequent cardiomegaly. In the investigation of possible immunological bases for the development of effusion, Shitara et al did not observe a correlation between the increased levels of proinflammatory cytokines in the fluid when compared to the serum. The authors concluded that tumor necrosis factor‐alpha (TNF‐α) and interleukin‐6 (IL‐6) could be involved in fluid retention by increasing the vascular permeability, whereas interleukin‐13 (produced by Th2 lymphocytes) may have played a role in the increase and recruitment of eosinophils into the pericardial fluid.…”
Section: Discussionmentioning
confidence: 99%
“… 10 It is also presumed that effusion could be related to an abnormal production of cytokines at the effusion site. 6 PE has been demonstrated to be in association with hypothyroidism and celiac disease in early childhood 3 14 15 16 but not in the perinatal period. Our case had both TMD and hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…TMD develops in 3 to 10% of newborns with DS, 5 is characterized by clonal proliferation of blast cells in blood/bone marrow and may be responsible for pericardial effusion. 1 2 4 6 7 8 9 10 11 12 13 Pericardial effusion in TMD may occur due to myocardial infiltration by degranulating eosinophils 13 or epicardial infiltration by atypical myeloid cells. 10 It is also presumed that effusion could be related to an abnormal production of cytokines at the effusion site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation